The Expression of Chemokines Is Downregulated in a Pre-Clinical Model of TTR V30M Amyloidosis - Moreira, João; Costelha, Susete; Saraiva, Margarida; Saraiva, Maria João (Frontiers in Immunology, 2021)
Inflammation is a hallmark of several neurodegenerative disorders including hereditary amyloidogenic transthyretin amyloidosis (ATTRv). ATTRv is an autosomal dominant neurodegenerative disorder with extracellular deposition of mutant transthyretin (TTR) aggregates and fibrils, particularly in nerves and ganglia of the peripheral nervous system. Nerve biopsies from ATTRv patients show increased cytokine production, but interestingly no immune inflammatory cellular infiltrate is observed around TTR aggregates. Here we show that as compared to WT animals, the expression of several chemokines is highly downregulated in the peripheral nervous system of a mouse model of the disease. Interestingly, we found that stimulation of mouse SCs with WT TTR results in the secretion of several chemokines, a process that is mediated by TLR4. In contrast, the secretion of all tested chemokines is compromised upon stimulation of SCs with mutant TTR (V30M), suggesting that V30M TTR fails to activate TLR4 signaling. Altogether, our data shed light into a previously unappreciated mechanism linking TTR activation of SCs and possibly underlying the lack of inflammatory response observed in the peripheral nervous system of ATTRv patients.